Vegetation Structure of Bukit Barisan Protected Forest I Sub DAS Lubuk Paraku Lubuk Kilangan District Padang City - Ramadhani, Suci; Leilani Eka Putri, Irma; Satria, Rijal; Kardiman, Reki (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Vegetation plays an important role in overcoming hydrological processes in an area, including protected forest areas. Changes in vegetation cover in protected forests will affect the water flow of a watershed ecosystem. However, there is still a lack of information about the vegetation structure of the Bukit Barisan I protected forest, so it is important to do research to find out the vegetation that makes up the Bukit Barisan I protected forest, the Lubuk Paraku Sub-watershed in Lubuk Kilangan District, Padang City. The research was conducted from November 2022 - March 2023. This type of research is descriptive using a survey method. For field data collection, the single plot method was used in 2 areas, the natural forest area and the forest adjacent to the garden. In each area, 3 single plot plots were made, 2 x 2 m plots for undergrowth and seedlings, 5 x 5 m for saplings, 10 x 10 m for poles, and 20 x 20 m for trees. Found at the seedling stage 145 individuals from 20 families, saplings 51 individuals from 10 families, pole stage 29 individuals from 10 families and tree stage 48 individuals from 12 families. The most individuals at the seedling level are included in the Araceae family, the most individual saplings and trees are included in the Moraceae family, the most individual pole stages are included in the euphorbiaceae family. Keywords: structure, protected forest, Lubuk Paraku watershed